2022
DOI: 10.3390/jpm13010043
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Dynamic Nomograms for Predicting Overall Survival and Cancer-Specific Survival in Breast Cancer Patients with Lung Metastases

Abstract: Background: 60–70% of patients who die from breast cancer have lung metastases. However, there is a lack of readily available tools for accurate risk stratification in patients with breast cancer lung metastases (BCLM). Therefore, a web-based dynamic nomogram was developed for BCLM to quickly, accurately, and intuitively assess overall and cancer-specific survival rates. Methods: Patients diagnosed with BCLM between 2004 and 2016 were extracted from the Surveillance, Epidemiology, and Final Results (SEER) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, the extended applicability of the nomogram was well demonstrated in the results of an external validation cohort from another region. Additionally, a web-based nomogram has the potential to facilitate the implementation process into clinical settings 53 . Notably, this study found that patients who benefited from PTR had a median postsurgical OS that was over three times longer than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extended applicability of the nomogram was well demonstrated in the results of an external validation cohort from another region. Additionally, a web-based nomogram has the potential to facilitate the implementation process into clinical settings 53 . Notably, this study found that patients who benefited from PTR had a median postsurgical OS that was over three times longer than those who did not.…”
Section: Discussionmentioning
confidence: 99%